Upaya Guru BK dalam Mencegah Bullying di SMPN 3 Pariaman - Lafziatul Sasriza; Zulkarnaini Zulkarnaini (Universitas 45 Surabaya, 2024)
This phenomenon occurs in students whoo carry out bully such as bullying, mocking, such as students who like to bully weak students, students who mock themselves with harsh, impolite words, students who insult each other with students, people who are involved in bullying, constantly isolated. The research results show that the efforts of Guidance and Counseling teachers at SMPN 3 Pariaman to stop harassment are first, by instilling the value of friendship among students and encouraging them to become active and participating members of society. Second, socialization and making posters where Guidance and Counseling teachers use poster media about bullying so that students are aware of the causes and consequences that arise as a result of bullying. Third, form an anti-bullying ambassador for each class, an ambassador who will help each class prevent student behavior that leads to bullying. Fourth, provide punishment in the form of depositing 30 juice memoranda for the perpetrators of bullying. Fifth, involve parents in the process of preventing bullying by providing socialization to parents by inviting parents to school or conveying it before taking student report cards.